Women to the fore - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Training programmes have been launched in Tanzania for women to start and run small food processing businesses. Sponsored by SIDO and UNIDO, they cover aspects of supply, processing of local products, hygiene and business management. So far, 347...